General toxicity and genotoxicity of altertoxin I: A novel 28‐day multiendpoint assessment in male Sprague–Dawley rats. Issue 8 (13th February 2022) - Zhu, Xia; Chen, Yiyi; Tang, Xinyao; Wang, Dongxia; Miao, Yeqiu; Zhang, Jing; Li, Ruirui; Zhang, Lishi; Chen, Jinyao
Abstract: The mycotoxin altertoxin I (ATX‐I) is one of secondary metabolites produced by Alternaria fungi and is frequently detected as food and feed contaminants. Little is known about the genotoxicity of the ATX‐I. In order to evaluate potential genotoxicity and general toxicity of ATX‐I, the novel 28‐day multiendpoint ( Pig‐a assay + micronucleus [MN] test + comet assay) genotoxicity platform was applied. Male Sprague–Dawley (SD) rats were randomized to five groups (six rats per group), that is, a positive control group ( N ‐ethyl‐ N ‐nitrosourea [ENU], 40 mg/kg.bw/d), two solvent control groups (PBS and corn oil), and two ATX‐I‐treated groups (low‐dose group [1.10 μg/kg.bw/d] and high‐dose group [5.51 μg/kg.bw/d]). Treatments were administered by oral gavage to male SD rats for 28 consecutive days. Histopathological damages in the liver, kidney, and spleen were observed, but without significant changes in hematological and serum biochemical parameters. Genotoxic endpoints indicated that ATX‐I could cause DNA damage. To summarize, in a relatively low‐dose range, ATX‐I may not have direct genotoxicity in vivo but could induce liver, kidney, and spleen damage. Abstract : General toxicity and genotoxicity of ATX‐I was evaluated with the multiendpoint assay in rats, combining the flow‐cytometric MN test, the comet assay, and the Pig‐a assay, and this is the first report of the in vivo genotoxicity of ATX‐I. The results indicated that constant exposure to ATX‐I could cause DNA damage and induce liver, kidney, and spleen damage.